Toxic masculinities in Virginia Phiri’s Desperate (2002) and Highway Queen (2010) - Njanji, Tendai M.L.; Hungwe, Elda (2017)
The article critiques the roles of men in prostitution and their attitude towards it. The article posits that it is not only the women who are involved in prostitution but that it takes two to prostitute. Through interrogating Phiri’s Desperate (2002) and Highway Queen (2010), when analysing the male roles and attitudes as well as the way they conduct themselves when they buy sex. Prostitution has become a thorny issue which in most circles is seen as a female domain where the term prostitute is usually loosely used to refer to females who sell sex. The question we pose , however, is that, how can women alone be labelled ‘prostitutes’ if there is no one they are prostituting themselves to? Thus the article seeks to examine and evaluate the roles of men in perpetuating prostitution as revealed by Phiri (2002;2010). That is, it examines how men create situations that force women into prostitution as well as their attitudes and actions in the process of prostitution. The Hegemonic Masculinity theory will inform our research.